Gambaran Variasi Anatomy Vena Saphena Parva pada Cadaver Indonesia - Danial Danial; Hary Nugroho; Eva Rachmi; Arie Ibrahim (ANATOMICA MEDICAL JOURNAL | AMJ, 2019)
Treatment of vein varicose that related to small saphenous vein is needed a good understanding of small saphenous vein anatomy and its’ variations. The purpose of this study investigates anatomy variations of small saphenous vein on Indonesians’ specimen base on cadaver dissected. We examine five pair of lower limb cadavers. Duplicating and branching patterns of small saphenous vein, and it’s relation to fascia were studied after exposing the superficial layers of the lower limb in Anatomy Laboratory of A.W Syahranie Hospital, Samarinda. This study found a small saphenous vein with accessory duplication in two pairs and a half of lower limb pair. In branching pattern, posterior crus region consist of two lower limbs with branch arise from 1/3 distal, one lower limb from 1/3 proximal and one lower limb from both in 1/3 distal and 1/3 medial. Small saphenous vein is located between the muscular fascia and superficial layer of membrane fascia in eight lower limbs. It can be said that this study get a clear describing of anatomy variations of small saphenous vein in Indonesian specimens base on cadaver dissected and also this study can support to further other research.